Perkembangan Sosial Emosional Anak Usia Dini dalam Berinteraksi dengan Teman Sebaya Kelas Darussalam Usia 5-6 Tahun di RA Ash-Shalihah - Sindy Fauziah; Fauziah Nasution; Nurlaili Nurlaili (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to describe how the social emotional development of young children interacts with peers Darussalam class for 5-6 years old at RA.Ash-Shalihah. The research method used is a descriptive method with a qualitative research approach, namely a problem solving procedure that is investigated by describing or explaining in a realistic way the condition of the subject or object of research. The results show that children's social emotional development in interacting with their friends is said to be good and teachers play an active role in this, teachers motivate, guide, advise, direct and provide understanding regarding using good language and not getting angry easily. Then there are supporting factors in children's social emotional development in interaction, namely parents, so that apart from being at school at home, children are also educated in using good language. However, the support found is that teachers never get tired and remain enthusiastic in approaching, mentoring and supervising students so that these students have better social emotional development in interacting with their friends.